A Case Study of Country Ownership Over Donor Aid: The Global Fund and the Ghanaian Country Coordinating Mechanism. Issue 2 (June 2022) - Onokwai, John Chukwuemeka; Matthews, Sally
Country ownership ostensibly gives aid-recipient countries more control over donor-funded programs. However, there is much debate both over the utility of the concept and its implementation. This article examines the operation of the Ghanaian Country Coordinating Mechanism (CCM) to determine to what extent the CCM enables country ownership. The CCM is a governance instrument designed to promote country ownership in relation to donor aid from the Global Fund, a key donor to the Ghanaian health sector. This case study shows that the operation of the Ghanaian CCM is reflective of conditional ownership, which limits recipient countries' exercise of control over donor-funded programs.